The gated communities as urban typology instrumentalized by financialization - Martínez-Toro, Pedro Martín (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
The relationships between the prevailing neoliberal capitalism and the proliferation of the type of residential complex closed as urban development strategy, are seen from the paradox of the cooperative and Community origin theories of utopian socialism (XIX century) and their exploitation from the seventies by industrial capitalism and since the nineties by globalized capitalism through the insatiable financial sector, in pursuit of higher profits, low risk and short return periods, in this an effective product. It is postulated that the “success” of the closed residential complex is associated with the processes of financialization of the global development through its manipulation by the financial sector, within the framework of a state arranged institutionally from the neoliberal ideology (principles and guidelines initiated in the “Bretton Woods” –1944– and consolidated in the so-called “Washington Consensus” –1989–. Such is the influence of the financial sector in the recent processes in production the metapolitan and metropolitan territory, particularly in the promotion, implementation and operation of closed residential complexes, there is an agreement in this process and called financialization, concluding that the structure, function and form of the development of the regional territory and the planetarium, which is materializing, with nuances owes much to the financialization processes. Methodologically the relationship between financial sector and construction from secondary sources in the construction sector is reviewed.